Preventative health, diversity, and inclusion: a qualitative study of client experience aboard a mobile health clinic in Boston, Massachusetts - Zoe Bouchelle; Yasmin Rawlins; Caterina Hill; Jennifer Bennet; Leonor Xochitl Perez; Nancy Oriol (International Journal for Equity in Health, 2017)
Abstract Background There are approximately 2000 mobile health clinics operating in the United States. While researchers have established that mobile health clinics can be cost effective and improve outcomes, there is scant research examining the healthcare experience on a mobile health clinic from patients’ perspectives. Methods Data were gathered from interviews with 25 clients receiving care on a Boston-based mobile health clinic and analyzed using grounded theory methodology. Results Emerging patterns in the data revealed three relational and three structural factors most significant to participants’ experience of care on The Family Van. Relational factors include providers who 1) Communicate understandably, 2) Create a culture of respect and inclusivity, and 3) Are diverse with knowledge of the community. Structural factors include 1) A focus on preventative health and managing chronic disease, 2) Expeditious, free, and multiple services, and 3) Location. Conclusions The participant accounts in this report serve to expand on prior research exploring mobile health clinics’ role in patients’ healthcare, to more clearly define the most salient aspects of the mobile health clinic model for the patients they serve, and to give voice to patients too seldom heard in the academic literature.